BS EN 3645-001. Aerospace series. Connectors, electrical, circular, scoop-proof, triple start threaded coupling, operating temperature 175 °C or 200 °C continuous. Part 001. Technical specification (29th July 2021) - British Standards Institution,
No abstract available